Kipper's rainy day - Inkpen, Mick. (San Diego, CA : Harcourt Brace, 2001)
Kipper the dog and most of his animal friends enjoy a rainy day.
Title taken from cover.
"Red wagon books."
"As seen on Nick Jr."
"Ages 2 to 5"--P. [4] of cover.
Keywords: Toy and movable books -- Specimens; Rain and rainfall -- Fiction; Dogs -- Fiction; Animals -- Fiction; Toy and movable books